2019
DOI: 10.3389/fimmu.2019.02190
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effect of Type I IFNs During Acute Lung Infection With Pseudomonas aeruginosa Is Mediated Through the Stimulation of Neutrophil NETosis

Abstract: Pseudomonas aeruginosa is an opportunistic multidrug-resistant pathogen, able to grow in biofilms. It causes life-threatening complications in diseases characterized by the up-regulation of type I interferon (IFN) signaling, such as cancer or viral infections. Since type I IFNs regulate multiple functions of neutrophils, which constitute the first line of anti-bacterial host defense, in this work we aimed to study how interferon-activated neutrophils influence the course of P. aeruginosa infection of the lung.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…In a positive feedback loop, these traps—which are composed primarily of DNA, high mobility group box protein 1 (HMGB1), and the cathelicidin antimicrobial peptide LL37—subsequently activate pDCs, which in turn produce more IFN-α via DNA binding to TLR9 [ 84 ]. Interferon-deficient mice have reduced production of NETs and reactive oxygen species (ROS), while recombinant IFN-β treatment restored NETosis [ 85 ]. Controlling this feedback loop may be a method warranting further examination in diseases that are exacerbated by excessive formation of NETs.…”
Section: Regulation Of Ifn Signaling In Neutrophilsmentioning
confidence: 99%
“…In a positive feedback loop, these traps—which are composed primarily of DNA, high mobility group box protein 1 (HMGB1), and the cathelicidin antimicrobial peptide LL37—subsequently activate pDCs, which in turn produce more IFN-α via DNA binding to TLR9 [ 84 ]. Interferon-deficient mice have reduced production of NETs and reactive oxygen species (ROS), while recombinant IFN-β treatment restored NETosis [ 85 ]. Controlling this feedback loop may be a method warranting further examination in diseases that are exacerbated by excessive formation of NETs.…”
Section: Regulation Of Ifn Signaling In Neutrophilsmentioning
confidence: 99%
“…Another therapeutic target related to NETs formation is Type I interferon. A recent finding suggests that Type I interferon-driven NETosis may promote respiratory P. aeruginosa infections in mice by providing a scaffold to support biofilm production [86]. Interruption of interferon signaling may, therefore, be useful for suppressing infection by biofilm-capable organisms, but care would need to be taken not to increase susceptibility to viral infection.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Infections with bacteria, such as P. aeruginosa , are often linked to the increase in type I IFN signaling in lung epithelial cells [ 47 ]. It has been demonstrated that type I IFN-mediated activation of neutrophils in lungs causes increase in NETosis, leads to the prominent tissue damage, and supports biofilm formation by P. aeruginosa and its persistence in the lung [ 48 ]. The role of PH in mediation of NETosis is also an important aspect [ 49 ].…”
Section: P Aeruginosa Induced Lung Epithelial mentioning
confidence: 99%